Prompt nuclear EMP and Synchrotron radiation: a resolution of two approaches - Roussel-Dupre, R.A. (IEEE transactions on electromagnetic compatibility, 2005)
The geomagnetic component of nuclear EMP generated by the prompt (t/sub max//spl sim/2 /spl mu/s) /spl gamma/-ray, neutron, and X-ray radiation from a nuclear explosion has been the subject of intense scrutiny for over 40 years. Recent work by certain members of the scientific community has suggested that a discrepancy exists in the calculations/derivation of nuclear EMP between treatments based on Maxwell's equations and the high-frequency approximation and those derived from a summation over particles emitting synchrotron radiation. In principle, the two approaches should be identical simply because the well-known Lie/spl acute/nard-Wiechert potentials for accelerating particles are derived from Maxwell's equations. In this paper, we start from the Lie/spl acute/nard-Wiechert potentials and derive an expression for nuclear EMP that is identical to previous work based on a solution of Maxwell's equations. Thus, the putative discrepancy between the two approaches is resolved and Maxwell's equations in this regard are again vindicated.